Financing for the Strengthening of SMEs, a Study in Guasave, Sinaloa, Mexico - Atondo Osuna, Jesus Francisco; Cabrera Montoya, Santa Xiomara; Castro León, Rubén Abel (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The access to financing for SMEs is limited, posing a barrier to their growth and development. The lack of financial resources hinders their competitiveness in a globalized scenario. Therefore, the objective of this research is to describe the financial environment of micro, small, and medium-sized enterprises (MSMEs) in the municipality of Guasave, Sinaloa, Mexico. The methodology involves a literature review and is contextualized based on the business environment of the region. The results reveal a lack of information and training for MSMEs to access financing. Additionally, credit institutions perceive risks in granting loans to companies with low production levels. Faced with this scenario of limited financial alternatives, the vulnerability of this productive sector in an increasingly globalized and demanding world is evident. Consequently, there is a need to reconsider financial policies, making access to various forms of leverage an achievable alternative for this universe of companies.